Corroboration of the Probative Value of Children's Testimony in Sexual Assault Cases Involving Minors in China - Wang, Ni (International Journal of Social Sciences and Public Administration, 2025)
In recent years, there has been a high incidence of cases of sexual assault on minors in China, most of which occur in a hidden environment. Due to delayed disclosure and loss of physical evidence, children's testimony often becomes the key evidence for both conviction and sentencing. Against this background, this paper examines the issue of the probative value of children's testimonies in Chinese cases of sexual abuse of minors, aiming to provide references for relevant legislation and judicial practice. Through a combination of case analysis, comparative study, and literature review, this paper systematically examines the current situation of Chinese judicial practice, international experiences, and theoretical developments. The study found that children's testimony often faces the dilemma of "solitary evidence" because of its inherent limitations and the particularity of cases, and its probative value is often questioned in sexual assault cases. The existing laws and regulations in China do not take this into account sufficiently, and the traditional mode of corroborating evidence is difficult to effectively compensate for the inherent defects of children's testimony. International experience demonstrates that the establishment of professional inquiry mechanism, a scientific assessment system and a multi-agency collaboration platform can help improve the credibility of children's testimony. Based on these findings, this study proposes to improve the existing system in four areas: constructing a credibility assessment system for children's testimony, establishing a professional inquiry mechanism, clarifying applicable rules for corroborating children's testimony, and strengthening multi-agency collaboration. This research is of great significance for promoting the specialization of juvenile justice in China, which not only helps to improve the trial quality and efficiency of sexual assault cases of minors but also provides institutional safeguards for protecting the legitimate rights and interests of minors.